Progress in heterocyclic chemistry. Vol. 17, A critical review of the 2004 literature preceded by two chapters on current heterocyclic topics - Gribble, Gordon W.; Joule, J. A. (John Arthur); ScienceDirect eBooks (Oxford : Elsevier, ., 2005)
This is the seventeenth annual volume of Progress in Heterocyclic Chemistry, which covers the literature published during 2004 on most of the important heterocyclic ring systems. The volume opens with two specialized reviews: Dennis Wright covers Furans as Versatile Synthons for Target-Oriented and Diversity-Oriented Synthesis; and John Hepworth and Mark Heron discuss 'The Synthesis and Photochromic Properties of Naphthopyrans'. The remaining chapters examine the recent literature on the common heterocycles in order of increasing ring size and the heteroatoms present. * Includes new contributions from experts in the field * Covers literature published during 2004 on most of the important heterocyclic ring systems * Presents reviews on Versatile Synthons for Target-Oriented and Diversity-Oriented Synthesis; and Synthesis and Photochromic Properties of Naphthopyrans.
Chapter 1: Furans as versatile synthons for target-oriented and diversity-oriented synthesis. -- -- Chapter 2: Synthesis and photochromic properties of naphthopyrans. -- -- Chapter 3: Three-membered ring systems. -- -- Chapter 4: Four-membered ring systems. -- -- Chapter 5: Five-Membered Ring Systems. -- -- Chapter 6: Six-Membered Ring Systems. -- -- Chapter 7: Seven-Membered Ring Systems. -- -- Chapter 8: Eight-Membered and Larger Ring Systems.
Includes index.
Print version record.
Elsevier
Keywords: Heterocyclic chemistry; Heterocyclic chemistry; Electronic books